Rationally Engineered Small Molecules: Pharmacophore Modeling and Molecular Docking Studies Targeting Toxic Polyglutamine (PolyQ) Repeats in Huntington’s Disease - Pradeepkiran, Jangampalli Adi; Vatapatri, Amardev Rajesh; Motakatla, Philip Irwin; Pasupuleti, Bhargavi; Munikumar, Manne (Current Drug Targets, 2025)
<span class=
Keywords: Huntington' s disease